The intrepid Canadian expedition - Pennypacker, Sara, 1951- (Flat Stanley's worldwide adventures ;, 2010)
While acting as a snowboard, Stanley Lambchop gets carried away by a strong wind, sending him and his new friend Nick on a cross-country Canadian adventure.